1993
DOI: 10.1111/j.1476-5381.1993.tb13785.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nitric oxide in the endothelium‐dependent relaxation induced by hydrogen peroxide in the rabbit aorta

Abstract: 1 The effects of hydrogen peroxide (H202, 0.1-1 mM) on the tone of the rings of rabbit aorta precontracted with phenylephrine (0.2-0.3 gAM) were studied.2 H202 induced a concentration-dependent relaxation of both the intact and endothelium-denuded rings. However, in the presence of intact endothelium, H202-induced responses were 2-3 fold larger than in its absence, demonstrating the existence of endothelium-independent and endothelium-dependent components of the vasorelaxant action of H202. 3 The endothelium-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
1
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 50 publications
5
72
1
2
Order By: Relevance
“…In the current study, we examined the short term implications of H 2 O 2 on eNOS activity in PAECs. We found that H 2 O 2 promotes NO bioactivity measured as the conversion of L-[ (38). The current study extends these findings by elucidating the mechanisms whereby H 2 O 2 can promote activation of eNOS.…”
Section: Discussionsupporting
confidence: 71%
“…In the current study, we examined the short term implications of H 2 O 2 on eNOS activity in PAECs. We found that H 2 O 2 promotes NO bioactivity measured as the conversion of L-[ (38). The current study extends these findings by elucidating the mechanisms whereby H 2 O 2 can promote activation of eNOS.…”
Section: Discussionsupporting
confidence: 71%
“…We found that low concentrations (100 nM-1 mM) selectively produced relaxation in endothelium-containing rings and this was abolished by L-NAME and methylene blue, inhibitors of nitric oxide synthase and soluble guanylate cyclase, respectively. This component of relaxation thus appeared to result from enhanced production of nitric oxide, as had previously been suggested (Furchgott, 1991;Zembowicz et al, 1993;Furchgott et al, 1994). Higher concentrations of hydrogen peroxide (30 4uM -1 mM), however, produced relaxation of endothelium-denuded rings and this too was inhibited by methylene blue suggesting involvement of soluble guanylate cyclase.…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, it has been found that the activity of SOD in various tissues is decreased in the diabetic state (Crouch et al, 1978;Loven et al, 1982; Matkovics et al, 1982;Cohen, 1995). On the other hand, it has been shown that hydrogen peroxide accelerates NO release (Rubanyi & Vanhoutte, 1986b), activates soluble guanylate cyclase activity, and causes smooth muscle relaxation (Zembowicz et al, 1993). Thus, an increase in SOD-induced relaxation in the diabetic state may be due to the overproduction of hydrogen peroxide which may cause smooth muscle relaxation, because diabetes causes a greater production of superoxide anion presumably due to reduced superoxide dismutase activity.…”
Section: Discussionmentioning
confidence: 99%